"It's all about opportunity": From professional contract to first-team regular. Issue 6 (2nd November 2022) - Swainston, Scott C.; Wilson, Mark R.; Jones, Martin I.
Abstract: The purpose of this study was to explore the junior to senior transition from professional contract to an established first-team player in an English men's professional football team. Six players were purposively sampled across four suggested phases of transition: preparation; orientation; adaptation; and stabilization. A series of three interviews explored their past and current experiences, as well as their future ambitions. Eight higher-order themes were developed using thematic analysis: performance culture; opportunity; organizational strategy; contracts; relationships; motivation; power dynamics; and dual career. Several general adaptation factors found in previous research were present, along with four unique findings. The current study sets the opportunity to play within the first team as the primary factor in career progression. Without the opportunity, a "gray period" develops when a player is in an undefined phase without specific goals. This complex transition is further complicated by the short-term nature of contracts, which influences motivation and the ability to see the big picture. Throughout the transition, receiving support from key stakeholders was challenged by their role as gatekeepers of playing time and future contracts. Organizations should seek to manage transitions through a hands-on approach, providing the necessary support throughout the gray period, while being aware of the limitations of support from those with power over opportunity. Future research should look to explore the suggested gray period and the challenges that develop without continual opportunity. Lay summary : Professional football players at different stages in their career discussed the challenges experienced in their journey to becoming a regular first-team player. Those players that were not getting the opportunity to play felt isolated and unable to discuss their concerns. Implications for football clubs managing this transition are discussed. IMPLICATIONS FOR PRACTICE: Providing opportunity in the senior team while managing players with no opportunity Availability and awareness of support systems outside of decision-makers